EFEKTIVITAS SENAM ERGONOMIK DAN KOMPRES HANGAT DALAM MENURUNKAN SKALA NYERI SENDI PADA LANSIA - Adinda Prasetyawati Putri; swito prastiwi; Moch. Zainol Rachman; Rossyana Septyasih; Edy Suyanto (Jurnal Keperawatan Terapan, 2022)
Joint pain occurs due to disorders in the joint area such as deformity, dislocation, sublocation or structural disruption around the joint. One of the nursing actions for pain management in a non-pharmacological way by using ergonomic exercise and warm compress. This study aims to determine the differences in the effectiveness of the level of pain before and after giving ergonomic exercise and warm compress to the elderly who experience joint pain at the Social Service Unit of Tresna Werdha Blitar in Tulungagung. The study design used a quasy experimental method. The sampling technique used was purposive sampling with a total of 30 respondents who were divided into three groups with control group. The test used is Paired T Test and Anova test with a confidence level of 95 percent. The results showed that the two treatments had an effect on reducing pain intensity in the elderly who experienced joint pain. The test results on giving ergonomic exercise and warm compresses showed a significant average difference with the control group in reducing pain with a p-value is 0.000. Both are equally effective in reducing pain. Suggestions for future researchers can develop research by examining joint pain patients such as factors that can affect joint pain such as daily physical activity.